Isolation of Dermatophytes from Infected Stray Dogs in Selangor, Malaysia - P.M Ridzuan; K. Proveen; Kamarulzaman Siti-Arffah (Jurnal Berkala Epidemiologi, 2021)
Background: Dermatophytosis is one of the most common skin diseases that affects cats and dogs. Geographic factors play an important role in determining prevalence, showing high rates of prevalence in warm and humid environments. Purpose: The aim of this study was to determine the macroscopic and microscopic identification of different types of dermatophytes present on stray dogs. Methods: The design of this study was laboratory-based research. Each sample was collected from an infection site (nail, hair, or skin) that was identified by conducting a physical examination of a stray dog that was infected with fungi. The skin scraping, nail clipping, and fur cutting samples were collected from infected dogs and then cultured on Sabouraud Dextrose Agar (SDA). The cultures were incubated at 26°C for five weeks. The isolates of fungi were then examined macroscopically and microscopically. The Lactophenol Cotton Blue (LPCB) staining technique was used for fungi morphology identification. Results: Overall, the most common type of dermatophytes that affected the dogs were Trichophyton spp. (64.70%), Aspergillus spp. (10.10%), Microsporum spp. (7.20%), and Curvularia spp. (5.60%). Conclusion: This study revealed the most common dermatophyte infections found on stray dogs in Selangor, Malaysia. This study can assist investigators in understanding the prevalence of the dermatophyte burden in stray dogs and help prevent further complication, such as the spread of illness, especially zoonotic infection.